'But She Doesn't DO Anything!' Framing and Containing Female Celebrity in the Age of Reality Television - Patrick, Stephanie (Université d'Ottawa / University of Ottawa, 2013)
This thesis offers a feminist analysis of the gendered public discourses surrounding notions of talent, authenticity and containment. Using two of the most polarizing stars in North America – ‘Snooki’ and Kim Kardashian – the author offers an analysis of how both hard and soft news frame our everyday understanding of women’s public work. Textual analyses of news articles demonstrated that displays of sexual power were most undermined by the media while attempts to venture beyond the reality television texts were contained. On the other hand, the news media were more likely to use positive framing when women were seen to be fulfilling more traditional roles such as wife and mother. The empirical research approach provides an original framework which can be applied to other female public figures to examine how such ideological and gendered discourses shape our understanding of women’s work as well as, more generally, women’s roles in our society.
Keywords: Reality television; Feminism; News; Discourse analysis; Authenticity; Talent; Containment; Celebrity